Peran Brand Awareness dan Kepercayaan dalam Membentuk Keputusan Nasabah Menggunakan Produk Tabungan Haji Usia Dini (U-DIN) di Bank Sumsel Babel Cabang Syariah Palembang - Lira Fitria Feruzia; Yusiresita Pajaria (CV. Era Digital Nusantara, 2025)
This study aims to evaluate the influence of brand awareness and trust on customers' decisions to use early age hajj savings at Bank Sumsel Babel, Sharia Branch, Palembang. This study is motivated by a phenomenon related to the influence of brand awareness factors and customer trust on their decisions to continue to choose to use early age hajj savings at Bank Sumsel Babel, Sharia Branch, Palembang. The population in this study includes all early age hajj savings customers at Bank Sumsel Babel, Sharia Branch, Palembang, and the research sample used was 119 with sampling using the G-power application. This research method is quantitative, with the main data used being the answers to the questionnaire distributed by the researcher. Data analysis was carried out using the SPSS software program assistance method. The results of the SPSS analysis show that Brand Awareness has a positive and significant effect on customer decisions. Trust has a positive and significant effect on customer decisions. Brand awareness and Trust simultaneously have a positive and significant effect on customer decisions. The higher the level of Brand awareness and customer trust in the bank, the higher the level of customer decisions in using early age hajj savings products at Bank Sumsel Babel, Sharia Branch, Palembang.